Parapelvic cysts, a distinguishing feature of renal Fabry disease. Issue 2 (28th March 2017) - Pisani, Antonio; Petruzzelli Annicchiarico, Luigi; Pellegrino, Angela; Bruzzese, Dario; Feriozzi, Sandro; Imbriaco, Massimo; Tedeschi, Enrico; Cocozza, Sirio; De Rosa, Dario; Mignani, Renzo; Veroux, Massimiliano; Battaglia, Yuri; et al.
Abstract: Background: Fabry's disease (FD) is a rare, multi-organ lysosomal disease, caused by the deficiency of the enzyme α-galactosidase A, and is difficult to diagnose. Although parapelvic cysts (PC) were previously associated with FD, their prevalence and significance are unclear. Methods: The present study aimed to: (i) evaluate, by renal ultrasound, the real prevalence of PC and of their determinants in a multicentre, nationwide cohort of FD patients ( n = 173, Study 1) and (ii) ascertain whether a greater accuracy of PC detection improved their identification, in FD patients from a single centre ( n = 67, Study 2). In both studies, for each FD patient, an age- and renal function-matched subject was selected for comparison (1:1). Results: In Study 1, PC were detected in 28.9% of FD subjects and in only 1.1% of control subjects (P < 0.001). The presence of other renal abnormalities did not differ between the groups, nor differences exist in the main demographic and laboratory parameters between the groups. In Study 2, the greater accuracy of ultrasound increased PC prevalence from 29.8% to 43.3% in the same subjects (P < 0.05). In both studies, no correlation was detected between PC and the main demographic, clinical and biochemical parameters, including use of enzyme replacement therapy (P < 0.1, minimum value). Finally, no difference existed between FD patients with and without PC. Conclusions: The present study suggests that the presence of PC in renal patients should alert physicians to consider the diagnosis of FD, primarily in subjects with an unclear family history of renal disease and in the presence of other stigmata of the disease.